Modulating oxone-MnOx/silica catalytic systems towards ibuprofen degradation: Insights into system effects, reaction kinetics and mechanisms - Yang, J.; Yuan, B.; Cui, H.; Wang, Shaobin; Fu, M. (Elsevier BV, 2017)
© 2016 Elsevier B.V.Heterogeneous processes activated persulfate for organic degradation is increasingly recognized as an environmentally important remediation technology. However, manipulating persulfate oxidation processes with desirable decontamination effectiveness is still underdeveloped. Towards this goal, we systematically investigated the catalytic behaviors of Oxone-MnOx/silica systems towards aqueous ibuprofen (IBU) degradation in terms of system effects, reaction kinetics and mechanisms. MnOx/SBA-15 (MS) demonstrated variable catalytic Oxone efficacies towards IBU removal at different solution pHs. Meanwhile, the catalyst supports and FeOx co-doping within MS also produced significant impacts on catalytic Oxone efficacy. Moreover, the catalytic Oxone efficacies of MS for IBU degradation were generally inhibited by humic acid, NO3-, HCO3-, SO42- and PO43- to different extents at low/high levels. Interestingly, Cl- at low concentrations (2 mM) obviously inhibited IBU removal by Oxone-MS, while Cl- at high concentrations (20 mM) greatly enhanced IBU removal. Kinetic studies implied that IBU removal by Oxone-MnOx/silica systems using two first-order kinetic models was closely related to the extents of the interferences of synthetic conditions and water chemistry components. The surface electron transfer between [tbnd]MnOx(OH)y species of MS and HSO5- of Oxone was responsible for the formation of reactive oxygen radicals, thus contributing to IBU degradation. Liquid chromatography–mass spectrometry was employed to identify oxidation products of IBU, and reaction pathways of IBU oxidation were accordingly proposed.